1977
DOI: 10.2527/jas1977.442266x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thawing Procedures on Fertility of Bovine Spermatozoa Frozen in .25-ml Straws

Abstract: The influence of thawing procedures on fertility of semen in .25-ml Continental 3 straws was investigated in a series of eight trials utilizing 1,634 cows. The following pregnancy rates were obtained: Trial 1, 38.6 vs 23.0% (P<.05) for semen thawed in 75 C water/7 sec vs "in the cow"; Trial 2, 29.7 vs 22.2% (P>.10) for semen thawed in 75 C water/7 sec vs "in the cow"; Trial 3, 82.8 vs 61.6% (P<.01) for semen thawed in 75 C water/7 sec vs "in the pocket"; Trial 4, 49.1 vs 45.9 (P>.10) for semen thawed in 75 C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Forde and Gravir detected a better sperm motility at high temperatures such as 60 and 80°C. Rugg et al (1977) obtained very high pregnancy rates of 56.0 and 55.3% in thawing techniques of 12 sec at 35°C and 7 sec at 75°C, respectively. Foote (1998) stated that thawing process must be carried out fast to minimize the damage caused by the changes in ice crystals during the unfreezing of the sperm, so that, the motility, acrosomal integrity and potential fertility are maintained in the best possible way.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Forde and Gravir detected a better sperm motility at high temperatures such as 60 and 80°C. Rugg et al (1977) obtained very high pregnancy rates of 56.0 and 55.3% in thawing techniques of 12 sec at 35°C and 7 sec at 75°C, respectively. Foote (1998) stated that thawing process must be carried out fast to minimize the damage caused by the changes in ice crystals during the unfreezing of the sperm, so that, the motility, acrosomal integrity and potential fertility are maintained in the best possible way.…”
Section: Resultsmentioning
confidence: 88%
“…It is suggested that the sperm should be thawed for 30-40 sec at body temperature during field studies Nur et al, 2003;Rugg et al, 1977). Unless a specific recommendation is given, thawing for 30-40 sec in a 33-35°C water bath is recommended, regardless of the diluent type and freezing procedure (DeJarnette et al, 2000;DeJarnette and Marshall, 2005).…”
Section: Resultsmentioning
confidence: 99%